Are Smoke and Aerosols Generated During Laparoscopic Surgery a Biohazard? A Systematic Evidence-Based Review. (August 2021) - Pasquier, Jorge; Villalta, Oscar; Sarria Lamorú, Sunaymy; Balagué, Carmen; Vilallonga, Ramon; Targarona, Eduardo M.
Background. Laparoscopic surgery generates end products that can have potentially harmful effects for the surgical team from short- or long-time exposure. In view of the current SARS-CoV-2 circumstances, controversy has risen concerning the safety of surgical smoke (SS) and aerosols and the perception of an increased risk of exposure during laparoscopic surgery. Methods. The present qualitative systematic review was conducted according to Meta-Analyses and Systematic Reviews of Observational Studies (MOOSE). A literature search was performed from March 2020 up to May 10, 2020, using the PubMed database, Cochrane, and Google Scholar to assess the risk of airborne transmission of viruses and the potential health risk of surgical smoke- and aerosol-generating procedures produced during laparoscopic surgery. The keywords were introduced in combination to obtain better search results. Application of the inclusion and exclusion criteria identified 44 relevant articles. Results. Genetic material from certain viruses, or the virus itself, has been detected in SS and aerosols. However, in the current SARS-CoV-2, as in other coronavirus situations, studies analyzing the presence of airborne transmission of viruses in surgical smoke are lacking. Conclusion . Despite the lack of clear evidence regarding the risk of diseases as the result of smoke- and aerosol-generating procedures during laparoscopic surgery, further investigation is needed. Meanwhile, all available precautions must be taken.